Anthropological Archaeology Underwater: Hunting Architecture and Foraging Lifeways beneath the Great Lakes. - Lemke, Ashley Kate (2016)
Hunter-gatherers are foundational to anthropology. Ethnographic accounts of foragers have been essential in building classic anthropological theories of human evolution, kinship, social organization, and religion. From these studies, a normative view of foragers as simple, highly mobile, egalitarian band societies with limited or no property/ownership, emerged and continues to be pervasive in the discipline. This larger issue frames the central problems addressed in this dissertation. It concerns hunter-gatherer societies and how they are effected by hunting architecture, such as drive lanes, animal corrals, and fishing weirs. These comparable built elements are found across time, space, and cultures because they are conditioned by similar traits in animal behavior. Subsistence strategies adopting such hunting features present a fundamental shift in exploitation by actively modifying the landscape (i.e. niche construction) to increase the yield and predictability of natural resources. It is argued that the creation and use of hunting architecture is among the most significant subsistence innovations in prehistory prior to the origins of agriculture; as similar to large-scale food production, the adoption of hunting architecture has demonstrable social and economic repercussions. This dissertation investigates the global phenomenon of hunting architecture by drawing on a regional case study – caribou hunting in the Great Lakes, where some of the oldest hunting structures (9,380-8,830 cal yr BP) have been submerged beneath Lake Huron. The preservation of a virtually unmodified, culturally engineered landscape underwater is an ideal laboratory for investigating broader issues. New underwater research conducted for this dissertation provides an unprecedented view of forager societies and hunting architecture in the past, problematizing our normative characterization of prehistoric hunter-gatherers. Ultimately, this dissertation makes contributions to three core areas; the local archaeological problem of Great Lakes ...